Optimalisasi Daya Tarik Wisata Melalui Kolaborasi Penthahelix di Brudjul Adventure Park - Setyawati, Harini Abrilia; Syarifudin, Akhmad; Huda, Miftahul (Politeknik Negeri Jember, 2024)
The development of tourist villages is in line with the spirit of establishing BUMDes to support village economic growth and prosperity. The aim of this community service activity (PKM) is to innovate the development of tourist villages to increase tourist attraction and create productive businesses as a new source of income for tourist villages. The activity period is June-Dec 2023 at the Brujual Adventure Park (BAP) tourist attraction Peniron tourist village, district. Pejagoan, Kebumen. The penthahelix approach is carried out by collaborating the roles of academy, business, community, government and media. The implementation method is by conducting outreach and discussions (FGD), training, providing facilitation , mentoring, and in the final phase conducting evaluation and measurement. The results show that the application of the penthahelix model in the Peniron tourist village is effective in increasing tourist attraction , creating new productive businesses, increasing the income of the tourist village, and providing economic benefits for the local community and the surrounding environment